2010
DOI: 10.1007/s10620-010-1280-8
|View full text |Cite
|
Sign up to set email alerts
|

Bax Predicts Outcome in Gastric Cancer Patients Treated with 5-fluorouracil, Leucovorin, and Oxaliplatin Palliative Chemotherapy

Abstract: Background Platinum and 5-fluorouracil (5-FU)-based regimens have been used the most frequently in palliative chemotherapy for gastric cancer. The present study evaluated the prognostic significance of Bax, excision repair cross-complementation group 1 (ERCC1), and thymidylate synthase (TS) in advanced gastric cancer patients treated with 5-FU, leucovorin, and oxaliplatin (FOLFOX) palliative chemotherapy. Methods Seventy-two patients with metastatic or recurrent gastric cancer were treated with FOLFOX regimen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…49 Low expression of Bax was also found to correlate with poor survival of patients with metastatic or recurrent gastric cancer who received FOLFOX chemotherapy. 50 Kang et al reported that low expression of Bax was the most significant predictor of poor survival in patients with esophageal cancer treated with fluorouracil and cisplatin with ratiotherapy. 51 Median survival was lower for Bax negative patients with transitional cell carcinoma of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…49 Low expression of Bax was also found to correlate with poor survival of patients with metastatic or recurrent gastric cancer who received FOLFOX chemotherapy. 50 Kang et al reported that low expression of Bax was the most significant predictor of poor survival in patients with esophageal cancer treated with fluorouracil and cisplatin with ratiotherapy. 51 Median survival was lower for Bax negative patients with transitional cell carcinoma of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…5 In such cases of unresectable and metastatic carcinomas, the outcome of cancer patients remains extremely poor and even total gastrectomy, the only curative approach providing the utmost survival advantage may prove to be inadequate. [6][7][8] Even though gastric cancer has, for a very long time, been considered as a chemo-sensitive tumor, at present there has not been a definitive standard of treatment in the advanced and adjuvant settings, since management patterns vary worldwide and the survival gain from current multimodality regimens appears to have to exert a pro-apoptotic function by sensitizing mouse embryonic fibroblasts to apoptotic stimuli induced by UV irradiation 34 or by promoting apoptosis in cisplatin-treated MDA-MB-231 breast carcinoma cells. 33 Furthermore, BCL2L12 was found to be differentially expressed at the mRNA level in a series of human malignancies with potential prognostic implications.…”
Section: Introductionmentioning
confidence: 99%
“…In two studies (Kwon HC et al, 2007;Kim KH et al, 2011), cases were defined as high expression on the condition that the grades of intensity and extent are both 2 or higher. In four studies (Cho et al, 2006;Kim et al, 2009;Choi et al, 2011;Jeong et al, 2011), from multiplying the grades of intensity by either the grades of extent or the percentage of stained cells, a IHC score was derived so as to dichotomize the levels of TS. In the remaining one study (Suda et al, 1999), the high expression were judged when the cytoplasm of cancer cells showed positive signals compared with stromal inflammatory cells.…”
Section: Evaluation Of Ts Methodologiesmentioning
confidence: 99%
“…Fifteen eligible studies assessed survival or treatment response in the advanced disease setting (Boku et al, 1998;Yeh et al, 1998;Miyamoto et al, 2000;Ichikawa et al, 2004;Tahara et al, 2004;Ichikawa et al, 2006;Boku et al, 2007;Kwon et al, 2007;Akamoto et al, 2008;Matsubara et al, 2008;Wei et al, 2008;Koizumi et al, 2010;Choi et al, 2011;Jeong et al, 2011;Jeung et al, 2011), with a total of 844 patients available for pooling (median: 62, range: 21-76). All studieds used fluoropyrimidine-containing regimens, either combination chemotherapy or monotherapy.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%